Analyze the Entry Modes of Foreign Retailers in China: A case study on Sainsbury’s - Liu, Shixiang (2011)
With a fast-growing economy that support a population of 1.5 billion, China is believed to hold promise as both an economic superpower and an enormous market in the twenty-first century. Meanwhile, the speed of retailer internationalization has increased dramatically throughout the world. As a result, the study of international retailing has developed from a position of observation, through one of analysis, to one of conceptual exploitation.